بيع الوفاء وتطبيقاته المعاصرة في المصرفية الإسلامية: دراسة تحليلية: (Selling Loyalty and Its Contemporary Applications in Islamic Banking: An Analytical Study) - محمد ضمير خالقيار; محمد صبري زكريا (At-Tajdid - Intellectual Refereed Journal, 2025)
This research aims to know the truth about the sale of loyalty and its modern applications in Islamic banks and financial institutions in the manner in which some financial institutions and Islamic banks deal in various fields with contemporary names, and jurists differ in explaining its ruling, dealing with it, and identifying it. Based on the fact that the approach followed in this study is the qualitative and analytical approach, therefore the research used books, scientific journals, and official articles in this article, and then analyzed them qualitatively. It is noted that the basic problem is that people want to keep their movable and immovable property, so if their property is sold, their ownership is cut off, so the option that gives them hope of recovering their property is the loyalty sale, and one of the most important things that can cause the problem in the schools of jurisprudence is the lack of a clear text from the Qur’an or the Sunnah in it, Then he points out that the contemporary uses and expressions of the opinions of contemporary jurists regarding the loyalty sale, the most important of which are: the (usurious) sale contract, the banker’s guarantee, the mortgage, and the real estate loan. The research has concluded that the loyalty sale is one of the formal contracts, as the buyer is required to fulfill it by returning the property. To the seller, when the seller returns the price to him, it is apparently a mortgage in the form of a sale, and it violates the provisions of the sales contract and its ruling, which benefits ownership of the sold item as a matter of permanence and stability. Keywords: Loyalty sale, contemporary applications, Islamic banking, analytical study.